VD_FINDINFO Réc-administrative / 2013 / 3 vom 27. März 2013 - VD Tribunal cantonal (2013)
RÉCUSATION, DÉLAI, RETARD, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE | 10 al. 2 LPA-VD, 11 al. 3 LPA-VD, 9 let. e LPA-VD